Periphery-functionalized porous organic cages - Reiss,PS; Little,MA; Santolini,V; Chong,SY; Hasell,T; Jelfs,KE; Briggs,ME; Cooper,AI (Chemistry, 2016)
By synthesizing derivatives of a trans-1,2-diaminocyclohexane precursor, three new functionalized porous organic cages were prepared with different chemical functionalities on the cage periphery. The introduction of twelve methyl groups (CC16) resulted in frustration of the cage packing mode, which more than doubled the surface area compared to the parent cage, CC3. The analogous installation of twelve hydroxyl groups provided an imine cage (CC17) that combines permanent porosity with the potential for post-synthetic modification of the cage exterior. Finally, the incorporation of bulky dihydroethanoanthracene groups was found to direct self-assembly towards the formation of a larger [8+12] cage, rather than the expected [4+6], cage molecule (CC18). However, CC18 was found to be non-porous, most likely due to cage collapse upon desolvation.